Three Solutions for a Singular Quasilinear Elliptic Problem. Issue 1 (14th February 2019) - Faraci, Francesca; Smyrlis, George
Abstract: In the present paper we deal with a quasilinear problem involving a singular term. By combining truncation techniques with variational methods, we prove the existence of three weak solutions. As far as we know, this is the first contribution in this direction in the high-dimensional case.